The truth about health care why reform is not working in America. - Mechanic, David, 1936- (Critical issues in health and medicine., 2008)
n The Truth about Health Care, David Mechanic explains how health care in America has evolved in ways that favor a myriad of economic, professional, and political interests over those of patients. While money has always had a place in medical care, "big money" and the quest for profits has become dominant, making meaningful reforms difficult to achieve. Mechanic acknowledges that railing against these influences, which are here to stay, can achieve only so much. Instead, he asks whether it is possible to convert what is best about health care in America into a well functioning system that better serves the entire population. -BOOK JACKET.